Modulatory effect of Kolin PlusTM, a polyherbal formulation on muscle growth development in choline deficient diet model of broilers: a genomic analysis using microarray - D'Souza, Prashanth; Marimuthu, Saravanakumar; Kaninathan, Arigesavan; Selvam, Ramasamy (International Journal of Scientific Reports, 2019)
Background: The present study was conducted to elucidate the genes and its associated pathways delineating the growth-promoting potential of polyherbal formulation (PHF), Kolin PlusTM using microarray in Cobb 430 broiler chickens. Methods: Microarray was performed for four groups, namely, normal diet (ND) as G1, choline chloride deficient (CCD) diet as G2, choline chloride (CCL, 400 g/ton) as G3 and PHF (400 g/ton) as G4. Breast muscle samples were collected, and the growth-related gene expression profile was measured using the Agilent microarray platform. Results: Totally 2900 differentially expressed genes (DEGs) in muscle tissue sample was revealed using hierarchical clustering based on the similarity of their expression profiles, which further allows the user to pick out groups of similar genes. Among them, 1000, 364 and 481 genes were significantly upregulated and 244, 485 and 326 genes were significantly downregulated between ND and CCD, CCL and CCD, PHF and CCD respectively. Furthermore, some of the focused genes (CSRP3, SOX10, BCO1, CALB1, LMOD2, KLF15, CTHRC1, PHGDH, UTS2R, and ANKRD2) were significantly (p<0.05) modulated by PHF (400 g/ton) supplementation in birds fed with CCD diet. These genes play an essential role in protein translation, energy metabolism, and muscle growth promotion. Conclusions:It may be concluded that supplementation of PHF at 400 g/ton of feed could positively influence the certain focused genes associated with muscle growth promotion, which favours the productive phenotypic response in broiler chickens fed with CCD diet.